Uma proposta metodológica para a determinação do indicador de contribuições harmônicas de agentes do sistema elétrico - Gianesini, Bárbara Morais (2024)
Electric power systems are composed of various components with operational properties that impact strongly on power quality indicators. Due to the increasing proliferation of nonlinear equipment at all levels of electrical systems, the harmonic distortion indicators have significantly risen, making issues related to these distortions more critical and frequent. Due to the potentially harmful effects of harmonics, these phenomena are subject to regulated limits that ensure the safe and reliable operation of electrical systems. Additionally, violations of these limits may require mitigation measures. However, it is known that the distortions measured at a given busbar result from the combination of harmonic emissions from various installations connected to the electrical system. With the goal of identifying the contributions of electrical agents to the existing distortions, the theme of harmonic contribution determination (HCD) arises. This area has been extensively explored in recent decades, but it is worth recognizing that there are still research gaps requiring further investigation and discussion. This includes the establishment of consistent, reliable, and effective HCD methods feasible for field application and the definition of an index for determining harmonic contributions in electrical power systems. In this context, this Ph.D. dissertation aims to advance in the studies and developments related to the proposition of a methodology that defines the agents’ harmonic contribution portions considering the operating dynamics of electrical systems over periods of analysis. The proposed methodology is composed of two parts: the establishment of a measurement campaign protocol for applying HCD methods on the busbars of interest, and the definition of the harmonic contribution index based on the statistical treatment of collected data from in the measurement campaign.